DATA SET: Modeling the geomagnetic response to the September 2017 space weather event over Fennoscandia using the Space Weather Modeling Framework: studying the impacts of spatial resolution - Dimmock, Andrw (10316372); Welling, Daniel (10316375) (2021)
The Space Weather Modeling Framework input files and virtual magnetometer output for the simulations described in " Modeling the geomagnetic response to the September 2017 space weather event over Fennoscandia using the Space Weather Modeling Framework: studying the impacts of spatial resolution ", submitted to AGU's Space Weather journal. See the README.txt for details